Pengaruh CAR dan BOPO Terhadap ROA pada Bank Syariah pada Tahun 2011-2018 - Aditya Surya Nanda; Andi Farouq Hasan; Erwan Aristyanto (Universitas Muhammadiyah Sidoarjo, 2019)
Risk based bank rating (RBBR) must always be monitored to avoid problems in the bank- ing system. The problematic conditions at a bank that can eventually end in bankruptcy can be identified as a measure of the company's tendency to financially fail and ultimately unable to carry out its business operations. Then analyzing the effect of the Capital Ade- quacy Ratio (CAR) and Operational Costs on Operating Income (BOPO) on performance (Return of Assets / ROA) on islamic banking is considered very important. The population of this study is Islamic Bangking and took samples of 2 banks in Indonesia for the period 2011- 2015. The sample method used is Purposive Sampling. From the results of the results analysis t test shows that the CAR variable partially does not affect the performance of islamic banking (ROA) while the BOPO variable has a significant effect on the performance of islamic banking (ROA). The results of the F Test analysis are known that the CAR and BOPO variables together have a significant effect on the performance of islamic banking. The results of the analysis of the Determination Coefficient (R2) obtained Adjusted Square (R2) of 0.969, this indicates that the performance of sharia banks can be explained by the variables CAR and BOPO of 96.90.